The healing of life within the HIV and AIDS pandemic: Towards a pedagogical reframing of paradigms concerning dysfunctional civil, health and ecclesial systems - Dames, Gordon E. (HTS Teologiese Studies / Theological Studies, 2013)
The inability of government, communities and churches to deal with complex HIV and AIDS challenges may foster pathological psychosocial and systemic dysfunctionalities. The reframing of pathological and disempowering pastoral therapeutic and health promotion praxes are sought. The objective was to construct a new pastoral and social therapeutic methodology. It should develop in line with health promotion praxes in strengthening both ecclesial and community health praxes. Reframing agents such as pastoral therapeutic and health praxes, as well as ecclesial and community systems, could ultimately engender a transformative process in transforming pathological HIV and AIDS praxes.
Free